PENGEMBANGAN MEDIA PEMBELAJARAN AKSARA JAWA INTERAKTIF BERBASIS MULTIMEDIA (Studi Kasus SD Mardi Rahayu 01 Ungaran) - Setiyo Adi Nugroho; Risti Wulandari (STEKOM PRESS, 2020)
SD Mardi Rahayu 01 Ungaran is an elementary school. The learning process still uses conventional methods which make students less enthusiastic in participating in learning and tend to get bored with the material presented. The purpose of this research is to develop interactive Javanese script learning media based on multimedia. The development method in this study uses the Research and Development method. Multimedia-based interactive Javanese script learning media is an alternative in the learning process. Based on the results of the validation, the learning media got a feasibility percentage of 92.5% from internal validator, 90% from external validator, and 81% from the results of user trials, so it can be concluded that the learning media developed was categorized as very feasible to use.